Update on anti-fibrotic pharmacotherapies in skeletal muscle disease. (February 2023) - Muraine, Laura; Bensalah, Mona; Butler-Browne, Gillian; Bigot, Anne; Trollet, Capucine; Mouly, Vincent; Negroni, Elisa
Abstract: Fibrosis, defined as an excessive accumulation of extracellular matrix, is the end point of a defective regenerative process, unresolved inflammation and/or chronic damage. Numerous muscle disorders (MD) are characterized by high levels of fibrosis associated with muscle wasting and weakness. Fibrosis alters muscle homeostasis/regeneration and fiber environment and may interfere with gene and cell therapies. Slowing down or reversing fibrosis is a crucial therapeutic goal to maintain muscle identity in the context of therapies. Several pathways are implicated in the modulation of the fibrotic progression and multiple therapeutic compounds targeting fibrogenic signals have been tested in MDs, mostly in the context of Duchenne Muscular Dystrophy. In this review, we present an up-to-date overview of pharmacotherapies that have been tested to reduce fibrosis in the skeletal muscle.